2018
DOI: 10.3762/bjoc.14.88
|View full text |Cite
|
Sign up to set email alerts
|

Fluorocyclisation via I(I)/I(III) catalysis: a concise route to fluorinated oxazolines

Abstract: Herein, we describe a catalytic fluorooxygenation of readily accessible N-allylcarboxamides via an I(I)/I(III) manifold to generate 2-oxazolines containing a fluoromethyl group. Catalysis is conditional on the oxidation competence of Selectfluor®, whilst HF serves as both a fluoride source and Brønsted acid activator. The C(sp3)–F bond of the mono-fluoromethyl unit and the C(sp3)–O bond of the ring are aligned in a synclinal relationship thereby engaging in stabilising hyperconjugative interactions with vicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The effects of the HF:amine ratio on Brønsted acid activation and in determining regioselectivity (geminal versus vicinal) is described in Table . The optimisation was initiated using previously reported conditions from this laboratory with commercially available Selectfluor as the terminal oxidant and a mixture of NEt 3 ⋅3 HF and Pyr⋅(HF) x as amine⋅HF sources. This system, which permits careful tuning of the acidity, proved to be instrumental in augmenting both conversion and selectivity.…”
Section: Figurementioning
confidence: 99%
“…The effects of the HF:amine ratio on Brønsted acid activation and in determining regioselectivity (geminal versus vicinal) is described in Table . The optimisation was initiated using previously reported conditions from this laboratory with commercially available Selectfluor as the terminal oxidant and a mixture of NEt 3 ⋅3 HF and Pyr⋅(HF) x as amine⋅HF sources. This system, which permits careful tuning of the acidity, proved to be instrumental in augmenting both conversion and selectivity.…”
Section: Figurementioning
confidence: 99%
“…Confidence in this approach stemmed from our recent vicinal and geminal difluorination of alkenes [ 26 30 ], and contemporaneous studies from the Jacobsen laboratory [ 31 34 ], under the auspices of I(I)/I(III) catalysis [ 35 37 ]. Moreover, elegant studies by Hara and co-workers have demonstrated that α-fluoroketones could be prepared by exposing silyl enol ethers to stoichiometric p -ToIIF 2 , in the presence of BF 3 ·OEt 2 and NEt 3 /HF 1:2 [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later, a synthetic route to 5-fluoromethyl-2-oxazolines from the readily accessible N-allylcarboxamides was developed via iodine(I)/(III) catalysis employing p-iodotoluene (10 mol%) as an organocatalyst and selectfluor as an oxidant. [32] Amine • HF serves as both fluoride source and Brønsted acid activator. The optimal amine/HF ratio (1:4.5) was easily obtained by combining the commercially available triethylamine tris(hydrogenfluoride) (Et 3 N • 3HF) and Olah's reagent (pyridine • HF).…”
Section: Amino- Oxy-or Carbofluorination Of Alkenesmentioning
confidence: 99%
“…Given the importance of fluorine substitution in drug discovery, this strategy provided a rapid entry into an important bioisostere class of bioactive 2-oxazoline scaffolds. [32] Very recently, iodine(I)/(III)-catalyzed direct fluorocyclization of aryl allyl ethers (76) with a simple C2symmetric iodoresorcinol catalyst in combination with selectfluor and amine • HF mixtures was disclosed by Gilmour and coworkers, forming biologically relevant enantio-enriched 3-fluorochromanes (77) with up to 7:93 e.r. value (Scheme 15).…”
Section: Amino- Oxy-or Carbofluorination Of Alkenesmentioning
confidence: 99%